Interactive parallel rendering of gigantic polygonal meshes on the grid architecture - Vergel de Dios, Jose Timoteo S
Rendering polygonal meshes is an important procedure in scientific visualization. This aids in the analysis of scientific data sets by generating a graphical representation of the data. This is compute intensive and requires dedicated graphics processors and memory. Rapidly growing data set sizes and the demand for applications with interactive rendering rate requirements create the need for a scalable rendering architecture. The goal of this research is to design, implement and test a rendering Grid that utilizes ordinary desktop computers, with limited amounts of main memory and no dedicated graphics processor, to render gigantic polygonal meshes with 10 to the 6th power to 10 to the 8th power graphics primitives at 25fps. Two data set formats, ePLY and GSplat, are implemented to render the polygonal meshes with varying levels of detail. Both formats are designed for out of core rendering and are ideal for parallelization.